Reliability of Chest Wall Mobility and Its Correlation with Lung Functions in Healthy Nonsmokers, Healthy Smokers, and Patients with COPD - Ravi S. Reddy; Khalid A. Alahmari; Paul S. Silvian; Irshad A. Ahmad; Venkata Nagaraj Kakarparthi; Kanagaraj Rengaramanujam (Canadian Respiratory Journal)
Chest wall circumference measurements are common evaluation methods in clinical settings by therapists in order to obtain chest wall mobility. Previous published results have been conflicting, and there is a lot of variability in the method of testing, which needs testing in different conditions. Seventy subjects (25 healthy nonsmokers, 25 healthy smokers, and 20 COPD) aged between 18 and 70 years participated in the study. Upper and lower chest expansion (CE) measurements (2 levels) are performed with cloth inch tape. Intrarater (between day) and interrater (within-day) reliability of CE measurements was evaluated by two examiners. Lung function parameters, forced expiratory volume in first second (FEV1), forced vital capacity (FVC), FEV1/FVC, and vital capacity (VC) were measured using a computerized spirometer (Spiro lab 3). The intrarater reliability for upper and lower CE showed very good agreement with intraclass correlation (ICC) values between 0.90 and 0.93 for upper CE and 0.85 to 0.86 for lower CE. The interrater reliability for upper CE showed good to very good agreement with ICC values ranging between 0.78 and 0.83, and lower CE showed very good agreement with ICC values ranging between 0.82 and 0.84. Upper and lower CE showed a significant and positive correlation with all lung function parameters, with strong correlation with FEV1/FVC (r = 0.68). Upper and lower CE measurements with inch tape showed good intra- and interrater reliability and reproducibility in healthy nonsmokers, healthy smokers, and COPD subjects. Compared to upper, lower CE correlated well with the lung function parameters. Upper and lower CE may be more useful in clinical practice to evaluate chest mobility and to give indirect information on lung function but interpretation with caution is required when considering implementation into clinical setting.